Heart Rate Variability in Patients with Rheumatoid Arthritis - Jahan, Kawser; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2013)
Background: Altered cardiovascular autonomic nerve function with impaired sympathovagal balance is found in rheumatoid arthritis (RA). Heart Rate Variability (HRV) analysis is an important tool for assessment of autonomic nerve activity. Objective: To assess cardiac autonomic nerve function status in patients with Rheumatoid arthritis (RA) by time domain measures of HRV. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January to December 2010. Sixty female RA patients, age range 18-50 years were constituted study group enrolled from the Out- patient Rheumatology Wing, Department of Medicine, BSMMU. Age matched thirty apparently healthy females were studied as control. Time domain measures of Heart Rate Variability (HRV) such as Mean RR intervals, Mean HR, SDNN, RMSSD, NN50% and PNN 50% were recorded for 5 minutes by a Polygraph machine to observe cardiac autonomic nerve function activity. Data were analyzed by independent sample t test. Results: Mean R-R interval, SDNN, RMSSD, PNN50%, NN50% were significantly lower (p<0.001) but heart rate was significantly (P<0.001) higher in rheumatoid arthritis patients. Conclusion: Cardiac autonomic nerve function is impaired and characterized by reduced resting parasympathetic activity in female Rheumatoid Arthritis patients. DOI: http://dx.doi.org/10.3329/jbsp.v7i2.14455 J Bangladesh Soc Physiol. 2012, December; 7(2): 78-82